Systemy wspomagania pracy grupowej w przedsiębiorstwach : badania wstępne - Wójtowicz, Radosław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The first part of the article presents definitions of several concepts, the most important for the discussed area. This part is also a synthetic attempt to categorise computer supported co-operative work systems. The second part of the article presents a description and results of a survey conducted in medium and large companies in Lower Silesia. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 276-283